A CASE STUDY IN GROSS PROFIT ANALYSIS. - Beckert, Ralph F.; Copeland, Ben R. (The Accounting Review, 1965)
Abstract This article focuses on the accounting method used in a gross profit computation. In order to remove the effect of sales price fluctuations, the variable rate used is based on the 1961 sales price. However, the 1962 rate is more indicative of present and future cost prices. Thus, either the 60% rate or the 54.5% rate, which is the 60% rate applied to 1961 sales dollars, appears to be the acceptable choice.